Integration of Servqual, KANO, and QFD for Hospital Service Quality Management: Integrasi Servqual, KANO dan QFD untuk Pengelolaan Kualitas Layanan Rumah Sakit - Wahyudi, Rahman Dwi; Rosiawan, Muhammad; Alda, Mamlu’atur Rahmawati (Universitas Muhammadiyah Sidoarjo, 2025)
Quality has become a research concern in the field of manufacturing or services. Currently, there are several tools available that can be used to improve service quality. Each tool has advantages and disadvantages, so integration between tools is needed to increase the effectiveness and efficiency of improvement efforts. Some tools that can be integrated to evaluate service quality comprehensively are SERVQUAL, KANO, and QFD. This scientific article provides experiential information on applying quality tool integration in the health sector. A hospital was selected as a case study for an example of the application of service quality improvement steps. The trial of SERVQUAL, KANO, and QFD integration in the case study showed that the integration of SERVQUAL and KANO selected 30% of critical service attributes that need improvement. Furthermore, QFD plays a role in executing the improvements effectively and efficiently.